On Velocity Magnetic Curves in Terms of Inextensible Flows in Space - Körpınar, Talat (AMER SCIENTIFIC PUBLISHERS, 2018)
In this work, we investigate inextensible flows of T-magnetic particles in space. Therefore, we obtain new results for inextensible flows T-magnetic curves of in space. Also, we characterize the inextensible of electric field by Lorentz equation. Finally, we obtain evolution equation of electric field in space.
Keywords: Magnetic Curve; Inextensible Flows; Frenet Frame